Transformation of Madrasah Governance Through The Implementation of Change Agents in Integrity Zone Development - Muhammad Suherman; Muh. Hanif (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2025)
Many consider it difficult for Islamic educational institutions to achieve integrity zones due to rigid bureaucratic culture and resistance to change. Previous studies have focused on the implementation of integrity zones in government institutions and madrasahs to improve services. However, the unique religious and cultural characteristics of madrasahs differ from public bureaucracies. This study aims to explore the role of Change Agents in developing integrity zones at Madrasah Aliyah Negeri 1 Cilacap, analyzing its contribution to strengthening governance based on good governance principles and Islamic moral values. Using a descriptive qualitative method with an exploratory case study approach, data was collected through interviews, observations, and secondary data reviews. Informants were selected purposively from MAN 1 Cilacap employees. The findings indicate that MAN 1 Cilacap has improved transparency and accountability through good governance principles and digital-based public services, including an information system for financial reporting, attendance, and online administrative services. The madrasah head has fostered shared commitment to a corruption-free environment, supported by a code of ethics and an integrity declaration. The integrity zone encourages behavioral transformation within the madrasah community, resulting in faster, more responsive, and satisfaction-based services, fostering an open, participatory culture focused on improving educational quality.